Kebijakan Retribusi Daerah: Analisis Potensi Pendapatan pada Tempat Rekreasi dan Venue Olahraga Komersial - Nanang Suparman; Muhammad Andi Septiadi (Universitas Merdeka Malang, 2022)
Regional levies are one of the sources of regional income that can fulfill finance regions to carry out their autonomy. Business service levies are fees for services provided by the government that are commercial in nature because basically these services can also be provided by the private sector. Recreation and sporting venues that are increasingly in demand by the community are example of business service fees that have significant potential to increase local income. The purpose of this study is to analyze the potential for levies for recreational and sports venues in Ciamis Regency, obstacles in determining potential levies for recreational and sports venues, as well as efforts made to increase the potential for levies for recreation and sports venues. The method used in this reseach is a qualitative methode with a case study approach. Data collection technique are carried out in several ways including observation, interviews, documentation and audio visuals. The result of data analysis conclude that the average revenue from recreation and sports in the last five years is still low around 3,66%, this means that a wider potential is nedeed, while at the level implementation of the collection there are several obstacles such as low public awareness, lack of facilities, and adequate infrastructure.